Virtual-world hospital simulation for real-world disaster response: Design and validation of a virtual reality simulator for mass casualty incident management - Pucher, Philip H; Batrick, Nicola; Taylor, Dave; Chaudery, Muzzafer; Cohen, Daniel; Darzi, Ara (The journal of trauma and acute care surgery, 2014)
Mass casualty incidents are unfortunately becoming more common. The coordination of mass casualty incident response is highly complex. Currently available options for training, however, are limited by either lack of realism or prohibitive expense and by a lack of assessment tools. Virtual worlds represent a potentially cost-effective, immersive, and easily accessible platform for training and assessment. The aim of this study was to assess feasibility of a novel virtual-worlds-based system for assessment and training in major incident response. Clinical areas were modeled within a virtual, online hospital. A major incident, incorporating virtual casualties, allowed multiple clinicians to simultaneously respond with appropriate in-world management and transfer plans within limits of the hospital's available resources. Errors, delays, and completed actions were recorded, as well as Trauma-NOnTECHnical Skills (T-NOTECHS) score. Performance was compared between novice and expert clinician groups. Twenty-one subjects participated in three simulations: pilot (n = 7), novice (n = 8), and expert groups (n = 6). The novices committed more critical events than the experts, 11 versus 3, p = 0.006; took longer to treat patients, 560 (299) seconds versus 339 (321) seconds, p = 0.026; and achieved poorer T-NOTECHS scores, 14 (2) versus 21.5 (3.7), p = 0.003, and technical skill, 2.29 (0.34) versus 3.96 (0.69), p = 0.001. One hundred percent of the subjects thought that the simulation was realistic and superior to existing training options. A virtual-worlds-based model for the training and assessment of major incident response has been designed and validated. The advantages of customizability, reproducibility, and recordability combined with the low cost of implementation suggest that this potentially represents a powerful adjunct to existing training methods and may be applicable to further areas of surgery as well.